Coblation tonsillectomy versus cold dissection tonsillectomy - Rashid, Tahir; Saeed, Imran; Riaz, Muhammad (Journal of Fatima Jinnah Medical University, 2020)
Post tonsillectomy pain and haemorrhage are important factors for the safety and efficacy of any surgical procedure. This study aimed to compare the efficacy of two surgical techniques i.e. coblator assisted tonsillectomy and time-tested gold standard operation of cold steel dissection tonsillectomy. Assessment of efficacy of coblator assisted tonsillectomy with cold steel dissection tonsillectomy. Patients and Methods: A prospective comparative interventional study was conducted on 100 patients. Coblation group included 50 patients while 50 patients were in cold dissection group. Following parameters like operative time, intraoperative bleeding amount, postoperative bleeding (secondary haemorrhage), postoperative pain, tonsillar fossa healing and time required to resume normal diet were compared. Results: In this study operation with coblator took shorter time with less per operative bleeding (p-value<0.001). For initial five days after surgery, patients who underwent coblation tonsillectomy experienced less pain as compared to dissection method (p-value<0.001). Coblation group also took less time to resume normal activity and diet. Conclusion: Coblation tonsillectomy appears to be a safe method. It is an effective procedure to reduce operative time and bleeding. It provides early healing of fossa with less postoperative pain. Being a new procedure, long term follow up studies will be required to analyze the long term outcomes.